Haemostatic management of cardiac surgical haemorrhage. (January 2015) - Besser, M. W.; Ortmann, E.; Klein, A. A.
Summary: Almost 30 000 cardiopulmonary bypass operations are performed in the UK every year, consuming a considerable portion of the UK blood supply. Each year, in cardiac surgery, 90% of blood products are used by only 10% of patients, and over the past 25 years, much innovation and research has gone into improving peri‐operative diagnosis and therapy for these patients. Visco‐elastic tests performed at the bedside, with modifications to allow direct quantification of fibrinogen levels, are probably the biggest advancement. There is no clear advantage of thromboelastometry over thromboelastography, and the published literature remains scarce. Visco‐elastic testing has recently been coupled with the systematic replacement of clotting factors by means of factor concentrates, with objective improvement in terms of blood loss, red blood cell usage and surgical re‐exploration. The National Institute for Health and Care Excellence has reviewed the available evidence and recommended visco‐elastic tests as cost effective in cardiac surgery. Factor concentrates, however, carry significant risks, particularly unnecessary donor exposures, potential selective over‐correction of partial deficiencies and the possibility that the postoperative risk of venous thromboembolism is increased; as yet there are no data on risk–benefit analysis. There are a number of promising drugs used in topical haemostasis, but the requirement to apply these before major bleeding is manifest limits their use considerably. Hyperfibrinolysis is less important than in the past due to the wide spread adoption of antifibrinolytic agents and close intra‐operative monitoring of heparin effect.